Zatoichi at the fire festival [videorecording (DVD)] - Misumi, Kenji, 1921-1975; Katsu, Shintarō, 1931-1997; Katsu, Shintarō, 1931-1997; Katsu, Shintarō, 1931-1997; Nakadai, Tatsuya, 1932-; Nishimura, Kō; Shimozawa, Kan, 1892-1968 (AnimEigo, 2003)
"In a town where women are bought and sold, Zatoichi stumbles upon a secret organization headed by Yamikubo, the Dark Imperial Lord. The 'Boss of Bosses,' blind like Zatoichi, takes an interest in the masseur, guiding him on the path of destiny and the duty of the sightless. However, a chance encounter with two beautiful women might be the end of Zatoichi, as both a jealous husband and the town Yakuza want his head!"--Container. Number 21 in the series.